Gênero e educação infantil: um estudo das atividades realizadas pelas professoras no contexto escolar - SOUSA, Thalita de Fátima Aranha Barbosa (2018)
In this study we seek to investigate the teachers' perceptions about the gender category, in order to identify how they work in the school context and what is the relationship in children’s education, between 3 and 5 years, in an Early Childhood school, in the city of São Luis (MA). Therefore, we have as objectives identify the gender perceptions of the teachers, in order to verify if such knowledge was worked in the teacher training; investigate how teachers insert gender issues in their practices; and to verify how these questions are practised in the school context, looking for their relation in the education of children from this study. Thus, we peform a qualitative research in an Early Childhood school in São Luis – MA. For the content analysis, as suggested by Bardin (2011), were used in the organization of the semi-structured interviews, and the field record. With the research it was able to understand that the pedagogical practice in this stage of education, Early Childhood, is still full by the pre-determined conceptions of being female or being male. However, it is considered that in Early Childhood Education it is possible to develop actions that problematize and contribute to the deconstruction and subsequent transformations in this theme, overcome, above all, binarism. Therefore, we consider relevant improvements in both teacher training and continuous education, so that they offer support and knowledge favorable to new positions.